Racial Segregation In The Metropolis: Comments On Racism, Health And Covid-19: observações sobre racismo, saúde e a covid-19 - Marques de Souza Oliveira, Regina; José de Oliveira, Reinaldo (Latitude, 2023)
In this text, we approach racial segregation in the metropolis of São Paulo, with racism, the health of the black population and Covid-19 as central. We interpret that racially based segregation is not something recent in the history of Brazilian cities, it has always existed, but due to the myth of racial democracy and structural racism, the sciences that observe the city and the urban turned exclusively to the context of social class inequalities. As a theoretical methodological procedure, we adopted the reading and interpretation of socioeconomic data from the 2010 IBGE and the literature on urban space and ethnic-racial relations. “The right to the city” in the national reality, in the national reality, in addition to the struggles over social class inequalities, implies the problematization and intersectionality of gender, ethnic-racial relations and the territory.